2014
DOI: 10.1007/s12032-014-0037-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the microRNA-29 family in patients with primary osteosarcomas

Abstract: The aim of this study was to facilitate and deepen the understanding of the associations of the microRNA-29 (miR-29) family with tumor progression and patients' prognosis of primary osteosarcoma. We examined expression levels of miR-29a, miR-29b, and miR-29c in tumor tissues and patients' sera of 80 cases of primary osteosarcomas by quantitative real-time reverse transcriptase-polymerase chain reaction. The correlations of their serum levels with clinicopathological characteristics and patient prognosis were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 34 publications
1
38
0
1
Order By: Relevance
“…The present data suggest that miR-506 is associated with the development and progression of osteosarcoma, and may be a promising diagnostic biomarker and therapeutic target for osteosarcoma. Recently, a study revealed that the miR-29 family are important in the development and progression of human osteosarcoma; serum levels of miR-29a and miR-29b were independent prognostic factors for overall and disease-free survival (9). Other studies have revealed that detection of serum miR-133b, miR-206, miR-148a, miR-196a and miR-196b expression has clinical potential as novel diagnostic biomarkers and are efficient predictors of prognosis in osteosarcoma patients (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present data suggest that miR-506 is associated with the development and progression of osteosarcoma, and may be a promising diagnostic biomarker and therapeutic target for osteosarcoma. Recently, a study revealed that the miR-29 family are important in the development and progression of human osteosarcoma; serum levels of miR-29a and miR-29b were independent prognostic factors for overall and disease-free survival (9). Other studies have revealed that detection of serum miR-133b, miR-206, miR-148a, miR-196a and miR-196b expression has clinical potential as novel diagnostic biomarkers and are efficient predictors of prognosis in osteosarcoma patients (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that miRs may be used as diagnostic biomarkers and may function either as oncogenes or tumor suppressors based on the effects of their target mRNAs (7,8). It has been reported in osteosarcoma that multiple miRs, including miR-29, miR-125b, miR-143 and miR-199a-3p, are involved in tumor growth, progression and metastasis (912). A previous study revealed that restoration of miR-506 in malignant transformed human bronchial epithelial cells suppressed cell proliferation (13).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, developing miR-29b-1 as a novel therapeutic agent might offer benefits for OS therapy. Paradoxically, it is reported that the levels of miR-29a, miR-29b, and miR-29c in OS tissues and patients' sera are significantly elevated compared with normal controls, and patients with higher serum levels of miR-29a and miR-29b have higher tumor grade, more positive metastasis and recurrence, and shorter overall survival and disease-free survival [84]. Although the reason for this discrepancy is unclear, it may have been caused by the experimental models and types of miRNAs.…”
Section: Additional Mirnasmentioning
confidence: 99%
“…cancers, including breast cancer, glioma, and colorectal carcinoma [21][22][23]. However, the relationship between miR-29a expression and CCA prognosis has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%